Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the quadratic equation [tex]\( 80x^2 + 92x - 84 = 0 \)[/tex], we can use the quadratic formula. The quadratic formula states:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] are the coefficients from the quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex].
For the given equation [tex]\( 80x^2 + 92x - 84 = 0 \)[/tex]:
- [tex]\( a = 80 \)[/tex]
- [tex]\( b = 92 \)[/tex]
- [tex]\( c = -84 \)[/tex]
First, calculate the discriminant [tex]\( \Delta \)[/tex]:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ \Delta = 92^2 - 4 \cdot 80 \cdot (-84) \][/tex]
[tex]\[ \Delta = 8464 + 26880 \][/tex]
[tex]\[ \Delta = 35344 \][/tex]
Next, we calculate the two possible values for [tex]\( x \)[/tex] using the quadratic formula:
[tex]\[ x_{1,2} = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substitute [tex]\( b \)[/tex], [tex]\( \Delta \)[/tex], and [tex]\( a \)[/tex] into the formula:
[tex]\[ x_1 = \frac{-92 + \sqrt{35344}}{2 \cdot 80} \][/tex]
[tex]\[ x_2 = \frac{-92 - \sqrt{35344}}{2 \cdot 80} \][/tex]
Simplifying these expressions, we get:
[tex]\[ x_1 = \frac{-92 + 188}{160} = \frac{96}{160} = \frac{3}{5} \][/tex]
[tex]\[ x_2 = \frac{-92 - 188}{160} = \frac{-280}{160} = -\frac{7}{4} \][/tex]
So the solutions to the equation [tex]\( 80x^2 + 92x - 84 = 0 \)[/tex] are [tex]\( x = \frac{3}{5} \)[/tex] and [tex]\( x = -\frac{7}{4} \)[/tex].
Thus, the correct answer is [tex]\( \boxed{x = -\frac{7}{4}, \frac{3}{5}} \)[/tex].
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex] are the coefficients from the quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex].
For the given equation [tex]\( 80x^2 + 92x - 84 = 0 \)[/tex]:
- [tex]\( a = 80 \)[/tex]
- [tex]\( b = 92 \)[/tex]
- [tex]\( c = -84 \)[/tex]
First, calculate the discriminant [tex]\( \Delta \)[/tex]:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ \Delta = 92^2 - 4 \cdot 80 \cdot (-84) \][/tex]
[tex]\[ \Delta = 8464 + 26880 \][/tex]
[tex]\[ \Delta = 35344 \][/tex]
Next, we calculate the two possible values for [tex]\( x \)[/tex] using the quadratic formula:
[tex]\[ x_{1,2} = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substitute [tex]\( b \)[/tex], [tex]\( \Delta \)[/tex], and [tex]\( a \)[/tex] into the formula:
[tex]\[ x_1 = \frac{-92 + \sqrt{35344}}{2 \cdot 80} \][/tex]
[tex]\[ x_2 = \frac{-92 - \sqrt{35344}}{2 \cdot 80} \][/tex]
Simplifying these expressions, we get:
[tex]\[ x_1 = \frac{-92 + 188}{160} = \frac{96}{160} = \frac{3}{5} \][/tex]
[tex]\[ x_2 = \frac{-92 - 188}{160} = \frac{-280}{160} = -\frac{7}{4} \][/tex]
So the solutions to the equation [tex]\( 80x^2 + 92x - 84 = 0 \)[/tex] are [tex]\( x = \frac{3}{5} \)[/tex] and [tex]\( x = -\frac{7}{4} \)[/tex].
Thus, the correct answer is [tex]\( \boxed{x = -\frac{7}{4}, \frac{3}{5}} \)[/tex].
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.